Finite Element Analysis (FEA) on Friction Stir Welding of Aluminium Alloy, AA5083 Using Coupled Eulerian-Lagrangian Model with Time-Scaling - Ismail, Syahmi (IRC, 2020)
Friction stir welding (FSW) is a unique method of welding that can produce high quality of joint. There are various process parameters that can influence the quality which includes the welding speed, rotational speed, axial force, tool design, tool tilt angle, plunge depth, pin design, material and friction coefficient. Many researches have been conducted to study the effect of varying those parameters values to the quality of the welded joint. Based on the previous researches, the thermal-related parameters are the main contributors that affect the quality of the joint. There are two main approaches to conduct a research on FSW process; experimental and numerical simulation/analysis. Numerical analysis has proven to be more advantageous compare to experimental approaches due to its ability to discretize a model into smaller element to perform mathematical analysis. It has made the study of properties especially those properties that can distribute throughout a material such thermal distribution and stress distribution become simple with less time and cost.